2013
DOI: 10.1002/smll.201303101
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Polymer Coatings: On‐Demand Drug Synthesis and Localized Therapeutic Effect under Dynamic Cell Culture Conditions

Abstract: Biocatalytic surface coatings are prepared herein for localized synthesis of drugs and their on-demand, site-specific delivery to adhering cells. This novel approach is based on the incorporation of an enzyme into multilayered polymer coatings to accomplish enzyme-prodrug therapy (EPT). The build-up of enzyme-containing multilayered coatings is characterized and correlations are drawn between the multilayer film assembly conditions and the enzymatic activity of the resulting coatings. Therapeutic effect elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Recently, we were the first to consider shear stress in the context of SMDD by analyzing biocatalytic films in the presence of shear stress using hepatocytes. [31] First, the goal was to compare the initial adhesion and spreading of endothelial cells on M n2 films considering shear stress. Microfluidic channels were coated with M n2 or PDA as control and the cells were allowed to adhere for 3 h before shear stress (t 4 ¼ 4 dyn cm À2 ) was applied for 3 h. The initial 3 h adhesion in the absence of shear stress was needed for the cells to adhere.…”
Section: Shear Stressmentioning
confidence: 99%
“…Recently, we were the first to consider shear stress in the context of SMDD by analyzing biocatalytic films in the presence of shear stress using hepatocytes. [31] First, the goal was to compare the initial adhesion and spreading of endothelial cells on M n2 films considering shear stress. Microfluidic channels were coated with M n2 or PDA as control and the cells were allowed to adhere for 3 h before shear stress (t 4 ¼ 4 dyn cm À2 ) was applied for 3 h. The initial 3 h adhesion in the absence of shear stress was needed for the cells to adhere.…”
Section: Shear Stressmentioning
confidence: 99%
“…Novelty of this presentation lies in that to the best of our knowledge, we provide the fi rst example of drug eluting biomaterials with a facile external control over the nature of the drug to be released (anti-infl ammatory, cytotoxic), drug dosage, and time of release. [ 15 ] This experimental setup also revealed that a more pronounced therapeutic effect was achieved locally, at the site of drug synthesis, compared to that observed on cells proliferating "downstream" from the location of drug release. [19][20][21]23 ] In doing so, our results signifi cantly extend functionality of these and other retained their enzymatic activity over as long as 7 days.…”
Section: Introductionmentioning
confidence: 80%
“…[ 12,13 ] Towards this end, we used an enzyme with excellent prior characterization in EPT techniques, β-Glucuronidase (β-Glu), [ 1,12 ] functionalized hydrogel biomaterials [ 13 ] and multilayered polymer coatings [ 14,15 ] with this enzyme, and subsequently used the resulting biomaterials as substrates for mammalian cell culture. We proposed to engineer the tools of EPT into biomaterials to achieve "substrate mediated enzyme prodrug therapy", SMEPT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the polyionic character of opposite charge could help to preserve the secondary structure when facing denaturating agents [4,15]. Enzymes in LbL films can increase their life-time and stability [16,17], which makes LbL an interesting option for biomedical applications such as enzyme prodrug therapy [16,18]. Since LbL has no restriction with respect to adsorbing substrate size and topology [19], protein multilayer films have been deposited on planar substrates, colloidal particles and membranes [4,20].…”
Section: Introductionmentioning
confidence: 99%